2011
DOI: 10.1590/s0102-09352011000400023
|View full text |Cite
|
Sign up to set email alerts
|

Utilização da glutamina, associada ao ácido glutâmico, sobre o desenvolvimento e a atividade enzimática em frangos de corte

Abstract: RESUMOAvaliou-se o efeito da glutamina, associada ao ácido glutâmico, proveniente de um produto comercial, sobre o desenvolvimento e a atividade enzimática em frangos de corte. Foram utilizados 800 pintos de corte, machos, de um a 42 dias de idade, distribuídos em cinco tratamentos, sendo quatro níveis de suplementação do Aminogut ® : 0,5; 1,5; 3,0 e 5,0% + uma dieta-controle, isenta do produto. Observou-se melhor índice de eficiência produtiva para os frangos alimentados com dietas suplementadas com 2,8% de A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
3
1
4
Order By: Relevance
“…In the present study, glutamine supplementation had no effect (P>0.05) on production viability for any of the periods evaluated in contrast with a study by Sakamoto et al (2011), who reported a quadratic effect of supplementation with glutamine associated with glutamic acid on productive efficiency, which rose by up to 2.8% with supplementation. In the present study, despite the absence of significant differences, production viability values were relatively low, probably because no antibiotics or anticoccidials were added to the diets in the early stages.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, glutamine supplementation had no effect (P>0.05) on production viability for any of the periods evaluated in contrast with a study by Sakamoto et al (2011), who reported a quadratic effect of supplementation with glutamine associated with glutamic acid on productive efficiency, which rose by up to 2.8% with supplementation. In the present study, despite the absence of significant differences, production viability values were relatively low, probably because no antibiotics or anticoccidials were added to the diets in the early stages.…”
Section: Resultscontrasting
confidence: 99%
“…Sakamoto et al (2011) found that supplementing glutamine in association with glutamic acid to broilers from 1 to 42 days of age had no effect on weight gain, feed intake, or feed conversion. Zavarize et al (2011) found no effects of supplementation on performance in the period from 1 to 42 days.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Se ejecutaron dos meta-análisis a partir de un total de 22 artículos científicos (1814 animales). (Avellaneda et al, 2008;Ayazi, 2014;Bartell & Batal, 2007;Dai et al, 2009;Dai et al, 2011;Fasina et al, 2010;Hu et al, 2016;Jazideh et al, 2014;Luquetti et al, 2016;Maiorka et al, 2016;Manvailer et al, 2015;Murakami et al, 2007;Muro et al, 2015;Mussini et al, 2012;Namroud et al, 2017;Nascimento et al, 2014;Nassiri Moghaddam & Alizadeh-Ghamsari, 2013;Olubodun et al, 2015;Ribeiro et al, 2015;Sakamoto et al, 2011;Soltan, 2009;Zavarize et al, 2011). Para explicar la heterogeneidad entre los estudios se realizaron meta-regresiones utilizando como covariables: nivel de inclusión de Gln (%), edad de inicio de suplementación (días), edad de evaluación (días), duración de la suplementación (días), número de repeticiones por tratamiento, número de pollos muestreados por unidad experimental (repetición), nivel de lisina (%) y proteína cruda en la dieta (%).…”
Section: Análisis Estadísticounclassified
“…Esse fato pode ser explicado pela falta de carboidratos no saco vitelino e a demora na secreção de PUBVET v.10, n.11, p.861-872, Nov., 2016 enzimas se deve a adaptação das secreções aos nutrientes ingeridos pelo pinto nas primeiras horas, sendo assim a α-amilase é substrato dependente (Tavernari and Mendes, 2009). Sakamoto et al (2011) descreveram que a maior atividade da amilase nas aves se dá aos 14 dias de idade, coincidindo com o maior crescimento do pâncreas. A ação diminui com o avançar da idade e o desenvolvimento máximo do pâncreas ocorre na segunda semana.…”
Section: Amilaseunclassified